1997
DOI: 10.1046/j.1570-7458.1997.00207.x
|View full text |Cite
|
Sign up to set email alerts
|

Semiochemistry of aposematic seed bugs

Abstract: (E)‐2,7‐Octadienyl acetate and (E)‐2‐octenyl acetate (1:10 by volume) were identified as a pheromone attractive to both sexes of the lygaeid bug, Tropidothorax cruciger. In a parallel investigation of Neacoryphus bicrucis (Lygaeidae), (E,E)‐2,4‐hexadienyl acetate and phenethyl acetate (≈9:1) were identified from males, and found attractive to both sexes of adults in the field plus a tachinid fly parasitoid of the bugs. In N. bicrucis, the pheromone was clearly shown to come from the tubular accessory glands of… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
32
0
1

Year Published

1998
1998
2018
2018

Publication Types

Select...
7
1

Relationship

0
8

Authors

Journals

citations
Cited by 37 publications
(33 citation statements)
references
References 25 publications
(33 reference statements)
0
32
0
1
Order By: Relevance
“…[15][16][17] MTG-derived attractant pheromones are either produced by males (in some Lygaeidae and Alydidae) 15,16,18 or females (Miridae, and some Alydidae), 17,[19][20][21][22][23] yet allomones are also stored in and released from the MTG reservoir in these species. 16,17,24 However, no sexual dimorphism was observed for the MTG secretions of P. macunaima adults.…”
Section: Discussionmentioning
confidence: 99%
“…[15][16][17] MTG-derived attractant pheromones are either produced by males (in some Lygaeidae and Alydidae) 15,16,18 or females (Miridae, and some Alydidae), 17,[19][20][21][22][23] yet allomones are also stored in and released from the MTG reservoir in these species. 16,17,24 However, no sexual dimorphism was observed for the MTG secretions of P. macunaima adults.…”
Section: Discussionmentioning
confidence: 99%
“…Low EAD responses together with unstable baselines result in low signal to noise ratios compared to lepidopteran species (Brézot et al 1994). Successful GC-EAG recordings have been made on heteropteran species, including an alydid (Leal et al 1995), seed bugs (Heteroptera: Lygidae) (Aldrich et al 1997), and stink bugs (Heteroptera: Pentatomidae) (Leal et al 1998;Dickens 1999;Weissbecker et al 2000). Innocenzi et al (1998) reported on GC-EAD recordings with the mirid Lygus rugulipennis, although no data were shown.…”
Section: Introductionmentioning
confidence: 99%
“…따라서, 톱다리개미허리노린재 성충을 포획하기 위한 가장 적합 한 페로몬 트랩은 피쉬트랩으로 설치높이는 지면으로부 터 60 cm 높이(콩 초장높이)에 설치하는 것이 가장 적당 한 것으로 생각된다. 끈끈이 트랩을 이용하여 톱다리개미허리노린재 (Mizutani et al, 1997), Leptocorisa chinensis (Leal et al, 1996), Tropidothorax cruciger (Aldrich et al, 1997)에 대하여 성충 유인력을 조사하였는데, 몸집이 큰 노린재는 스스로 트랩에서 탈출할 수 있기 때문에 비효율적이라고 하였다 (McBrien and Millar, 1999). 특히, 노린재과(pentatomid) 에 속하는 노린재류는 트랩의 안쪽이 어둡고 밀폐되면 천천히 걸어 들어가는 특징이 있다고 하였다 (Mizell and Tedders, 1995;James et al, 1996).…”
unclassified